Breaking The Cycle: Reforming Indonesia’s Justice System to Prioritize Victim-Centered Solutions - Amriyanto, Amriyanto; Alting, Husen; Bakhtiar, Handar Subhandi; Putra, Grahadi Purna (Jurnal Dinamika Hukum, 2024)
This study examines the role and position of crime victims within Indonesia's criminal justice system, highlighting their marginalization and the limitations of the current framework. Victims are often relegated to the role of evidence providers, sidelining their rights and needs while exposing them to risks such as retaliatory actions and psychological trauma. The system's emphasis on punitive measures for offenders fails to adequately address the suffering of victims, perpetuating their exclusion from meaningful participation in justice processes. The research employs a normative legal method, drawing on statutory and conceptual approaches alongside legislative analyses and secondary data, to explore restorative justice as a viable solution. Restorative justice offers a balanced, inclusive model that involves victims, offenders, and their families in collaborative decision-making. This approach not only addresses victims’ needs and aspirations but also reflects Indonesia’s cultural values of kinship and social harmony. It emphasizes fairness by holding offenders accountable in a manner proportionate to their capacity, while promoting victim rehabilitation and community reconciliation. Findings demonstrate the potential of restorative justice to mitigate systemic challenges, enhance victim involvement, and create outcomes aligned with societal values. The novelty lies in advocating for restorative justice as a culturally congruent and legally viable alternative to the prevailing adversarial system. By prioritizing victim-centered justice, this approach fosters a more humane and effective criminal justice process, ensuring that justice serves all stakeholders equitably.Keywords: Criminal Justice System; Restorative Justice; Victims.